Development of Warehouse Data Models to Support JNE Delivery Services - Ekowati, Maria Atik Sunarti; Dananti, Kristyana (Universitas Muhammadiyah Surakarta, 2021)
In order to help improving the performance of JNE business communities in this globalization era, it is necessary to encourage them to compete with each other in acquiring technology to support all their work activities so that they can be carried out as effectively and efficiently as possible, due to the increasingly dominant role and technology. The data warehouse is one of the concepts oriented to the core components of a business, that is, data can be categorized as a strategic supporting aspect because through the formation of a data warehouse an output can be obtained in the form of a report that can be used as analysis material for the executive in the decision-making process. The objectives to be achieved in this research are to formulate a data warehouse model and application design in accordance with the results of the needs analysis, which can support JNE business actors as a delivery service, as a case study JNE Klaten is used as research object. The methodology used in this study uses analysis and design methods. The method of analysis is carried out by studying literature, conducting surveys and interviews, identifying information needed by executives in decision making, and defining data warehouse requirements which will be built based on Nine-Steps Methodology. The design method is carried out by designing a data warehouse application, as a display interface that contains supporting features from the user side. The results of the research are in the form of data warehouse models and applications that are built based on operational data, which are processed in various dimensions, so that they can form a report to meet the needs of the executive about information and using the data warehouse, the executive can analyze the reports generated from multiple viewpoints easily, and can also be used as a reporting tool.